Bisexual, pansexual, queer: Non-binary identities and the sexual borderlands - Callis, April Scarlette (Sexualities, 2014)
This article focuses on sexualities in the USA that exist within the border between heterosexuality and homosexuality. I first examine the usefulness of applying borderland theory to non-gay/non-straight sexualities such as queer and bisexual. I then give an ethnographic analysis of sexual self-identities on the borders, shedding light on how participants envisioned labels such as ‘pansexual,’ and ‘heteroflexible.’ Finally, I explore the ways that the sexual borderlands became tangible in Lexington, Kentucky at certain events and locations. Throughout, I highlight the ways that the sexual borderland touches on all sexualities, as individuals knowingly cross, inhabit, or bolster sexual identity borders.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; anthropologie; approches et analyses; discipline; identités LGBTQIA2+; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexologie; sexualité; thématiques; états-unis; étude qualitative

Sex, desire and masturbation : An interpretative phenomenological analysis of sexual health education for young women - Hanson, Jodie (Manchester Metropolitan University, 2014)
British, Sex and Relationship Education has been condemned by Ofsted as ‘not yet good enough’ (2013:6). Previous literature would suggest this is through the absence of desire based knowledge. Other research would highlight the issue of masturbation as a construct to the improvement of the sexual health. However, as genital masturbation is often a taboo within feminine culture the current study used Interpretative Phenomenological Analysis (Smith, 1996, 1999) to assess the intrinsic values of six young women regarding their sexual health and desires. Participants ranged in sexual knowledge from undergone several years of sexual health education to limited sexual health education; forming the basis for the current national education system. Analysis of the data revealed three master themes: pleasure conflict, ‘That Girl’ complex and sexual discourse. A working model of sexual health needs was then proposed in order to address the hierarchy of erotic plasticity the participants showed. Ramifications of socio-political implications towards feminine desire and masturbation are detrimental to sexual health improvement.
https://e-space.mmu.ac.uk/576583/1/Jodie%20Hanson.pdf
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; discipline; europe; jeunes femmes*; masturbation féminine; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; éducation sexuelle; études qualitatives